Pain in the spine and upper limbs among double bass players - Szczechowicz, Jakub; Kania, Marta (Health Promotion & Physical Activity, 2019)
Aim of the study: The aim of this study was to analyse pain occurring in double bass players within the upper limb and spine. Materials and methods: Two groups were compared depending on the length of time the instrument was played and the anatomical structures that were subjected to the greatest loads were considered. A group of 50 musicians of different ages from 17 to 31 years old was included in the study. In order to obtain data on the frequency, location and nature of pain, a self-prepared questionnaire was used in electronic form. The survey was designed on the basis of available questionnaires used to study the diseases of instrumentalist musicians (Standardized Nordic questionnaires for the analysis of musculoskeletal symptoms and Evaluation of Performing Artist). Respondents answered questions not only about pain, but also factors that can significantly affect their course. The analysis of lifestyle or level of awareness in the field of occupational hazards and prevention was included in 30 open-ended and closed questions. Results: The results indicate a high percentage of double bass players suffering from pain. The most common pain in the surveyed double bass players it turned out to be pain in the lumbo-sacral segment, shoulder girdle, wrist and hand. The duration of the game had a negative impact on the severity of pain symptoms, which were often accompanied by other symptoms such as pain radiation, loss of concentration, or difficulties in making precise movements. Conclusions: It can be concluded that music work is subject to certain occupational risk and affects on the health of the musicians.